Condições de saúde de pacientes do gênero feminino com dependência química - Lins, Samira Ambar; Gaetti-Jardim, Ellen Cristina; Ciesielski, Francisco Isaac Nicolas [UNESP]; Aguiar, Rosangela Conceição Miotti de Souza; Schweitzer, Christiane Marie; Gaetti-Jardim Júnior, Elerson [UNESP] (My University, 2010)
This study evaluated the general and oral health conditions of female patients included in a program for recovering drug addiction and patients who did not use drugs. By means of anamnesis and medical history, as well as medical and dental assessments, the health conditions of 160 patients were assessed; 80 presented drug dependence and 80 do not use drugs. The most frequently used drugs were tobacco, alcohol, and crack, usually in associations. The patients presenting chemical dependence had increased frequency of behavioral changes, as well as several diseases involving the immune and cardiovascular systems, detaching infectious and inflammatory reactions and delay in the process of tissue repair. In the oral cavity, it was verified a high occurrence of periodontitis and gingivitis. Chemical dependence showed to be associated to a high frequency of infections, arthritis, hypertension and behavioral changes, which normally would not be noted by health professionals, but that could compromise the results of medical and dental treatments.

O presente estudo avaliou as condições gerais e bucais de saúde de pacientes do gênero feminino mantidas em um programa para recuperação de dependentes químicos e de pacientes que não utilizaram esses compostos. Utilizando-se de anamnese, avaliações médicas e odontológicas, as condições de saúde de 160 pacientes foram examinadas, das quais 80 apresentavam dependência química e 80 não utilizavam drogas. As drogas mais consumidas foram o tabaco, álcool e crack, quase sempre em diferentes associações. As pacientes com dependência química apresentaram freqüência aumentada de altera- ções comportamentais, além de diferentes enfermidades envolvendo os sistemas imunológico e cardiovascular, com destaque para as de reações inflamatórias e infecciosas e retardo no processo de reparo tecidual. Na cavidade bucal, verificou-se maior ocorrência de periodontite e gengivite. A dependência química mostrou estar associada a uma maior freqüência de infecções, artrites, hipertensão arterial e modificações comportamentais, que normalmente não seriam alvo de maior atenção por parte de profissionais de saúde, mas que comprometeriam os resultados dos tratamentos médicos e odontológicos.
Keywords: Oral health; Microbiology; Street drugs; Saúde bucal; Microbiologia; Drogas ilícitas; Oral health; Microbiology; Street drugs